Effect Of Financial Factors On Financial Performance With Moderating Role Of Firm Size: Evidence From Listed Manufacturing Sector - Dr. Aftab Hussain Tabasam; Shahid Mahmood; Dr. Ch. Kamran Mahmood; Samra Hassan; Dr. Lubna Zafar; Nosherwan Sarwar (Kurdish Studies, 2024)
This study examines how financial factors, with firm size acting as a moderating factor, affect the performance of listed manufacturing firms in Pakistan. The panel data set has been used in the current study. Data collection for analysis took place between 2014 and 2023. Furthermore, the data has been obtained from reputable firms' websites as well as the Pakistan Stock Exchange's website. Size was selected as the moderating variable for this study. Financial leverage, asset tangibility, activity ratio, and effectiveness ratio were independent variables. The effect has been examined using the most credible regression analysis models, which include the fixed-effect, random-effect, and pooled OLS models. The most appropriate model was selected as Fixed effed based on a few tests. The findings reveal that financial leverage has a significant but negative relationship with profitability. In addition, Tang, Effcency, and Activity are positive and significant influences on profitability. The findings show that the link between ROA and moderating variable size is moderated. Thus, Size has a substitution effect on leverage, while activity exhibits a complementing effect.